Androgens mediate sexual dimorphism in Pilarowski-Bjornsson Syndrome - Anderson, Kimberley Jade; Thorolfsdottir, Eirny Tholl; Nodelman, Ilana M; Halldorsdottir, Sara Tholl; Benonisdottir, Stefania; Alghamdi, Malak; Almontashiri, Naif; Barry, Brenda J; Begemann, Matthias; Britton, Jacquelyn F; Burke, Sarah; Cogne, Benjamin; et al. (medRxiv, 2025)
Sex-specific penetrance in autosomal dominant Mendelian conditions is largely understudied. The neurodevelopmental disorder Pilarowski-Bjornsson syndrome (PILBOS) was initially described in females. Here, we describe the clinical and genetic characteristics of the largest PILBOS cohort to date, showing that both sexes can exhibit PILBOS features, although males are overrepresented. A mouse model carrying a human-derived Chd1 missense variant (Chd1 R616Q/+) displays female-restricted phenotypes, including growth deficiency, anxiety and hypotonia. Orchiectomy unmasks a growth deficiency phenotype in male Chd1 R616Q/+ mice, while testosterone rescues the phenotype in females, implicating androgens in phenotype modulation. In the gnomAD and UK Biobank databases, rare missense variants in CHD1 are overrepresented in males, supporting a male protective effect. We identify 33 additional highly constrained autosomal genes with missense variant overrepresentation in males. Our results support androgen-regulated sexual dimorphism in PILBOS and open novel avenues to understand the mechanistic basis of sexual dimorphism in other autosomal Mendelian disorders.
Keywords: Sex differences; CHD1; Mendelian disease; Neurodevelopmental disorder